Insight on extraction and characterisation of biopolymers as the green coagulants for microalgae harvesting - Ang, T.-H. (MDPI AG, 2020)
This review presents the extractions, characterisations, applications and economic analyses of natural coagulant in separating pollutants and microalgae fromwater medium, known as microalgae harvesting. The promising future of microalgae as a next-generation energy source is reviewed and the significant drawbacks of conventional microalgae harvesting using alum are evaluated. The performances of natural coagulant in microalgae harvesting are studied and proven to exceed the alum. In addition, the details of each processing stage in the extraction of natural coagulant (plant, microbial and animal) are comprehensively discussed with justifications. This information could contribute to future exploration of novel natural coagulants by providing description of optimised extraction steps for a number of natural coagulants. Besides, the characterisations of natural coagulants have garnered a great deal of attention, and the strategies to enhance the flocculating activity based on their characteristics are discussed. Several important characterisations have been tabulated in this review such as physical aspects, including surface morphology and surface charges; chemical aspects, including molecular weight, functional group and elemental properties; and thermal stability parameters including thermogravimetry analysis and differential scanning calorimetry. Furthermore, various applications of natural coagulant in the industries other than microalgae harvesting are revealed. The cost analysis of natural coagulant application in mass harvesting of microalgae is allowed to evaluate its feasibility towards commercialisation in the industrial. Last, the potentially new natural coagulants, which are yet to be exploited and applied, are listed as the additional information for future study. Â© 2020 by the author.